Developing Medibang Paint-Based Digital Comic for Teaching Narrative Text - Hidayati, Khafidoh; Christanti, Ana (Nusantara Educational Review, 2024)
This research is based on the limited use of English learning media, causing students to often get bored because of the monotonous learning atmosphere. This research aims to make learning more exciting and interactive by developing digital comic learning media based on Medibang Paint. This research uses the RnD (Research and Development) method using the ADDIE development model. The media expert validation results were 81.25% in the "practical" category, and the material expert validation results were 97.9% in the "very valid" category, so it can be concluded that these digital comics are practical and very valid for use in English learning text material. Narrative. The results of the student response questionnaire were 79.8% in the "practical" category. Based on the results of this implementation, digital comics based on Medibang Paint are practical for students to use in learning English with narrative text material. Penelitian ini berlatar belakang pada penggunaan media pembelajaran bahasa Inggris yang terbatas, menyebabkan siswa sering bosan karena suasana pembelajaran yang monoton. Tujuan dari penelitian ini adalah membantu untuk proses pembelajaran lebih menarik dan interaktif dengan mengembangkan media pembelajaran komik digital berbasis Medibang Paint. Penelitian ini menggunakan metode RnD (Research and Development) dengan menggunakan model pengembangan ADDIE. Hasil validasi ahli media sebesar 81,25% dengan kategori "praktis" dan hasil validasi ahli materi sebesar 97,9% dengan kategori "sangat valid", sehingga dapat disimpulkan bahwa komik digital ini praktis dan sangat valid untuk digunakan pada pembelajaran bahasa Inggris materi teks naratif. Hasil dari lembar angket respon siswa adalah 79,8% dengan kategori "praktis". Berdasarkan hasil implementasi tersebut, dapat disimpulkan bahwa komik digital berbasis Medibang Paint ini praktis untuk digunakan siswa dalam proses pembelajaran bahasa Inggris materi teks naratif.